2004
DOI: 10.2355/isijinternational.44.1793
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Surface Tension Measurements of Liquid Metals Having Low Capillary Constants by the Constrained Drop Method

Abstract: Accurate measurements of surface tension of liquid metals having low capillary constants (the ratio between density (r) and surface tension (s), r/s) have been attempted using the constrained drop method. High accuracy of surface tension measurements was obtained by making a large axi-symmetric liquid drop and adopting a developed image capturing system composed of a high-resolution charge-coupled device (CCD) camera, an additional CCD camera to adjust the level of the metal drop and a He-Ne laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 34 publications
2
29
0
2
Order By: Relevance
“…Further details pertaining to this constrained drop method have been previously reported. 13,18) Following experimentation, the sample was subjected to chemical analysis using an ICP-AES and an oxygen analyzer. In addition, the interface between the sample and the alumina crucible was investigated using a Scanning Electron Microscope (SEM, Hitachi, S-4300) and an Energy Dispersive X-ray Spectroscope (EDX, Horiba, EX-200).…”
Section: Electromagnetic Levitation Methodsmentioning
confidence: 99%
“…Further details pertaining to this constrained drop method have been previously reported. 13,18) Following experimentation, the sample was subjected to chemical analysis using an ICP-AES and an oxygen analyzer. In addition, the interface between the sample and the alumina crucible was investigated using a Scanning Electron Microscope (SEM, Hitachi, S-4300) and an Energy Dispersive X-ray Spectroscope (EDX, Horiba, EX-200).…”
Section: Electromagnetic Levitation Methodsmentioning
confidence: 99%
“…The apparatus and experimental techniques have been described in Ref. 16. The experimental measurements were compared with the calculation results.…”
Section: )mentioning
confidence: 99%
“…1, reported measurements are also drawn for comparison. 16,[18][19][20][21][22][23][24][25][26][27][28][29][30] Keene 30) asserted in his review that the surface tension of liquid metal measured using the sessile drop method could be lowly estimated due to the contamination from the substrates (mainly oxides), and the surface tension measured by the levitation method usually showed higher surface tension values than that by the sessile drop method because the sample in the levitation method might not be contaminated from the substrate. However, Egry et al 29) showed that the surface tension of liquid metal droplets measured by the levitation method had been highly estimated due to the electromagnetic pressure on the liquid metal.…”
Section: Surface Tension Of Pure Liquid Ag Cu and Snmentioning
confidence: 99%
See 1 more Smart Citation
“…In two sets of the previous experiments, however, the surface tension value for pure liquid iron was lowly estimated than the more reliable recent data (1 842(Ϯ44) 7) mN/m at 1 823 K). It is considered that the samples used in the experiments might have been contaminated by surface-active impurities such as oxygen and sulfur, which may considerably lower the surface tension of liquid iron-based alloys.…”
Section: Introductionmentioning
confidence: 60%